2012
DOI: 10.1016/j.chemosphere.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Debrominated, hydroxylated and methoxylated metabolism in maize (Zea mays L.) exposed to lesser polybrominated diphenyl ethers (PBDEs)

Abstract: Debrominated, hydroxylated and methoxylated metabolism in maize (Zea mays L.) exposed to lesser polybrominated diphenyl ethers (PBDEs) Sen" Debromination, hydroxylation and methoxylation of PBDEs in plant occurred rapidly. " The introduction of a hydroxyl/methoxy group at the ortho-positions was easier. " PBDEs are more susceptible to metabolism in leaves and stems than in roots." P MeO-PBDEs concentration was significantly higher than P OH-PBDEs concentration. a r t i c l e i n f o a b s t r a c tA hydroponi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 44 publications
5
27
1
2
Order By: Relevance
“…Furthermore, the concentrations of the individual OH-PBDEs were also significantly correlated to their corresponding MeO-PBDE congeners (4 0 -OH-BDE17 and 4 0 -MeO-BDE17, 3 0 -OH-BDE28 and 3 0 -MeO-BDE28, 3-OH-BDE47 and 3-MeO-BDE47, 5-OH-BDE47 and 5-MeO-BDE47, 6-OH-BDE47 and 6-MeO-BDE47, 2 0 -OH-BDE68 and 2 0 -MeO-BDE68, 6-OH-BDE85 and 6-MeO-BDE85, respectively) in the soils (P < 0.05). Significant correlations were also obtained in our previous hydroponic experiment between 3-OH-BDE28 and 3-MeO-BDE28, OH-BDE47 and MeO-BDE47 in maize (P < 0.05, Wang et al, 2012). It was therefore speculated that OH-PBDEs and MeO-PBDEs may share to some extent a common source or similar bioaccumulation behavior in the soils and plants.…”
Section: The Composition and Distribution Of Oh-pbdes And Meo-pbdes Isupporting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, the concentrations of the individual OH-PBDEs were also significantly correlated to their corresponding MeO-PBDE congeners (4 0 -OH-BDE17 and 4 0 -MeO-BDE17, 3 0 -OH-BDE28 and 3 0 -MeO-BDE28, 3-OH-BDE47 and 3-MeO-BDE47, 5-OH-BDE47 and 5-MeO-BDE47, 6-OH-BDE47 and 6-MeO-BDE47, 2 0 -OH-BDE68 and 2 0 -MeO-BDE68, 6-OH-BDE85 and 6-MeO-BDE85, respectively) in the soils (P < 0.05). Significant correlations were also obtained in our previous hydroponic experiment between 3-OH-BDE28 and 3-MeO-BDE28, OH-BDE47 and MeO-BDE47 in maize (P < 0.05, Wang et al, 2012). It was therefore speculated that OH-PBDEs and MeO-PBDEs may share to some extent a common source or similar bioaccumulation behavior in the soils and plants.…”
Section: The Composition and Distribution Of Oh-pbdes And Meo-pbdes Isupporting
confidence: 51%
“…However, ortho-substituted OH-PBDEs and MeO-PBDEs have also been detected in PBDE exposure plants and animals (Qiu et al, 2007; Wang et al, 2012;Sun et al, 2013b), and meta-and parasubstituted compounds have also been found in environmental matrices Qiu et al, 2009;Sun et al, 2013a;Zhang et al, 2012). In the present study the ortho-, meta-and para-substituted OH-PBDEs and MeO-PBDEs were all detected in the soil and plant samples with 6-OH-BDE47, 6-OH-BDE85, 2 0 -OH-BDE3, 6 0 -OH-BDE99, 3 0 -OH-BDE7, 6-MeO-BDE85 and 2 0 -MeO-BDE3 as the major congeners (Figs.…”
Section: The Composition and Distribution Of Oh-pbdes And Meo-pbdes Imentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxylated PBDEs (OH-PBDEs) and methoxylated PBDEs (MeO-PBDEs) have also been identified in various environmental media (Ueno et al, 2008;Wang et al, 2014) and biological samples (Kelly et al, 2008;Teuten et al, 2005). Their origin is far from clear, and increasing evidence has shown the existence of transformation of PBDEs to OH-PBDEs and MeO-PBDEs (Stapleton et al, 2009;Sun et al, 2013a;Wang et al, 2012). Debrominated PBDEs, OH-PBDEs and MeO-PBDEs have greater potencies for some adverse effects such as embryo developmental toxicity (Boxtel et al, 2008), genotoxicity (Ji et al, 2011) and endocrine disrupting effects (He et al, 2008;Meerts et al, 2001;Wiseman et al, 2011) than their precursor PBDEs, and may bring additional adverse influences to bear on the environment and human health; therefore their formations and behaviors in the environment have received increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high importance, studies on the behavior of PBDEs in terrestrial plants are very limited, particularly regarding the biotransformation of PBDEs, OH-PBDEs and MeO-PBDEs in plants. In our previous work, transformation of PBDEs to lower brominated PBDEs, OH-PBDEs and MeO-PBDEs in plants was observed (Huang et al, 2010;Wang et al, 2012). Sun et al (2014) recently reported the reciprocal transformation between OH-PBDEs and the corresponding MeO-PBDEs in young whole pumpkin plants by a hydroponic experiment.…”
Section: Introductionmentioning
confidence: 99%